A study of the narrator in Nonnus of Panopolis' Dionysiaca : storytelling in late antique epic - Geisz, Camille, 1985- (Amsterdam Studies in Classical Philology, 2017)
This Study of the Narrator in Nonnus of Panopolis' Dionysiaca by Camille Geisz investigates manifestations of the narratorial voice in Nonnus' account of the life and deeds of Dionysus (4th/5th century C.E.). Through a variety of interventions in his own voice, the narrator reveals much about his relationship to his predecessors, his own conception of story-telling, and highlights his mindfulness of the presence of his narratee. Narratorial devices in the Dionysiaca are opportunities for displays of ingeniousness, discussions of sources, and a reflection on the role of the poet. They highlight the innovative style of Nonnus' epic, written as a compendium of influences, genres, and myths, and encompassing the influence of a thousand years of Greek literature.